An iron-based solid-state energy storage device and a method for preparing the same

By using reduced graphene oxide/Fe2O3 electrodes and redox cement-based electrolytes in energy storage devices, the problem of poor circulation stability of existing energy storage devices is solved, and high energy and high power energy storage effects are achieved, which are suitable for applications in the construction field.

CN115910615BActive Publication Date: 2025-02-28TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211365226.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-03
Publication Date
2025-02-28
Estimated Expiration
2042-11-03

AI Technical Summary

Technical Problem

The existing energy storage devices have poor cycle stability when meeting high energy and high power requirements, which limits their application in the construction field.

Method used

Reduced graphene oxide/Fe2O3 electrode and redox cement-based electrolyte were used to improve the conductivity and cyclic performance of the electrode by growing Fe2O3 nanocubes in situ on the foam nickel matrix, and K3[Fe(CN)6] was added to the cement-based composite electrolyte, and redox reaction was introduced to improve capacitance performance.

Benefits of technology

It significantly improves the electrochemical performance and cyclic stability of the energy storage device, expands the voltage window, and improves the energy density, making it suitable for high-performance energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The present invention relates to an iron-based solid-state energy storage device and a preparation method thereof, wherein the energy storage device comprises a redox cement-based electrolyte and a reduced graphene oxide / Fe 2 O 3 Electrode; First, a simple hydrothermal method was used to synthesize reduced graphene oxide / Fe 2 O 3 electrode, and then prepare a redox cement-based electrolyte at room temperature, and finally mix the redox cement-based electrolyte and the reduced graphene oxide / Fe 2 O 3 The electrode assembly obtains an energy storage device. The present invention in situ grows Fe on a foam nickel substrate loaded with reduced graphene oxide. 2 O 3 Nanocubes, using the synergistic effect between nanomaterials to improve the performance of reduced graphene oxide / Fe 2 O 3 Electrochemical properties of electrode materials. In addition, adding K 3 [Fe(CN) 6 ], using the redox reaction of Fe(CN) 6 3‑ / Fe(CN) 6 4‑ The high solubility and electrochemical activity of the cement-based solid electrolyte improve the electrochemical energy storage performance without affecting the mechanical properties. The energy storage device prepared by the present invention has a wide voltage window and high electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of building energy storage and electrochemical technology, and specifically relates to an iron-based solid-state energy storage device and a preparation method thereof. Background Art

[0002] In recent years, the construction industry accounts for about 40% of global energy consumption, and reducing building energy consumption has become an imminent energy issue around the world. "Zero-energy buildings" have gradually become the goal of future buildings, aiming to use solar energy to offset energy consumption in buildings. However, current energy storage devices have certain limitations and cannot meet the application of large-scale buildings. Therefore, how to make energy storage devices meet high energy and high power requirements at the same time without sacrificing cycle life has become a major challenge in practical applications.

[0003] Iron and its oxides are commonly found in reinforced concrete. Iron electrodes have natural conditions for utilization and low preparation costs. In addition, iron electrodes are environmentally friendly and insoluble in alkaline solutions. They are very popular in the field of construction engineering applications, making the development of high-energy, safe and cheap energy storage devices have great potential. However, the power density of iron electrodes is low and the cycle stability is poor, which seriously limits their practical application. Therefore, it is of great significance to find nanocomposite electrode materials based on iron and its oxides. Summary of the invention

[0004] The purpose of the present invention is to provide an iron-based solid-state energy storage device and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solution: an iron-based solid-state energy storage device, comprising a redox cement-based electrolyte and a reduced graphene oxide / Fe 2 O 3 Electrode; the reduced graphene oxide / Fe 2 O 3 The electrode is composed of nickel foam, reduced graphene oxide and Fe 2 O 3 The redox cement-based electrolyte comprises polyacrylic acid, potassium hydroxide, K 3 [Fe(CN) 6 ] and cement-based composite materials; the redox cement-based electrolyte is located between two reduced graphene oxide / Fe 2 O 3 between electrodes.

[0006] Furthermore, the cement is silicate cement.

[0007] Furthermore, the redox cement-based electrolyte comprises cement, polyacrylic acid, potassium hydroxide, K 3 [Fe(CN) 6] and deionized water in a mass ratio of (100-300):(20-80):(10-50):(0-4):(15-90).

[0008] Since the overall performance of the energy storage device is limited by the electrode and electrolyte materials, it is necessary to start from both the electrode and the electrolyte to broaden the voltage of the energy storage device and improve the capacitance performance. 4 ,KI,VOSO 4 , hydroquinone, K 3 [Fe(CN) 6 ], etc., the reversible oxidation / reduction reaction electron transfer at the electrode / electrolyte interface is an effective way to improve the specific capacitance of energy storage devices. Therefore, the use of redox reaction of Fe(CN) 6 3- / Fe(CN) 6 4- Due to the high solubility and electrochemical activity of K, adding K to cement-based composite electrolyte materials 3 [Fe(CN) 6 ], thereby improving the capacitive performance of the energy storage device.

[0009] The second object of the present invention is to provide a method for preparing an iron-based solid-state energy storage device, comprising the following steps:

[0010] (1) Reduced graphene oxide / Fe 2 O 3 Preparation of the electrode: ferric chloride dihydrate, sodium acetate, deionized water and ethanol are mixed and stirred to obtain a mixed solution; graphene oxide is ultrasonically dispersed in deionized water to obtain a graphene oxide suspension, which is then coated on the surface of a nickel foam substrate, and dried to obtain a nickel foam coated with graphene oxide on the surface; then the nickel foam coated with graphene oxide on the surface is subjected to a hydrothermal reaction with the mixed solution to obtain a reduced graphene oxide / Fe 2 O 3 Semi-finished electrode; finally, the graphene oxide / Fe 2 O 3 After the electrode semi-finished product is washed and dried, the reduced graphene oxide / Fe 2 O 3 electrode;

[0011] (2) Preparation of redox cement-based electrolyte: Polyacrylic acid, potassium hydroxide and K 3 [Fe(CN) 6 ] is dissolved in deionized water, and stirred evenly to obtain a polyacrylic acid mixed solution; the polyacrylic acid mixed solution is then mixed with cement and stirred evenly, and then poured into a mold to obtain a flowing redox cement-based electrolyte;

[0012] (3) Reducing the reduced graphene oxide / Fe 2 O 3 The electrodes are inserted into both sides of the mold containing the redox cement-based electrolyte in a flowing state obtained in step (2), and then placed in a curing room for curing, curing, and demoulding to obtain the iron-based solid-state energy storage device.

[0013] Furthermore, the mass ratio of ferric chloride dihydrate, sodium acetate, deionized water and ethanol in the mixed solution described in step (1) is (0.338-1.014):(1.014-3.042):(5-40):(15-50), and the stirring time of the mixed solution is 40-90 min.

[0014] Preferably, the stirring time of the mixed solution is 60 to 80 minutes.

[0015] Furthermore, the concentration of the graphene oxide suspension in step (1) is 5 to 20 mg mL -1 .

[0016] Preferably, the concentration of graphene oxide suspension is 10-15 mg·mL -1 .

[0017] Furthermore, the drying temperature of the nickel foam coated with graphene oxide in step (1) is 40-80° C., the temperature of the hydrothermal reaction is 160-200° C., the time of the hydrothermal reaction is 8-20 hours, and the reduced graphene oxide / Fe 2 O 3 The drying temperature of the electrode semi-finished product is 40-60°C, and the drying time is 2-6 hours.

[0018] Preferably, the drying temperature of the nickel foam coated with graphene oxide is 40-60°C.

[0019] Furthermore, the concentration of reduced graphene oxide loaded on the surface of the nickel foam in step (1) is 0.05 to 0.5 mg cm -2 , Fe loaded on the surface of nickel foam 2 O 3 Concentration: 0.5-2 mg cm -2 .

[0020] Preferably, the concentration of reduced graphene oxide loaded on the surface of nickel foam is 0.1-0.2 mg·cm -2 , Fe loaded on the surface of nickel foam 2 O 3 Concentration: 0.9~1.0mg·cm -2 .

[0021] Furthermore, the stirring time of the polyacrylic acid mixed solution and cement in step (2) is 5 to 30 minutes.

[0022] Furthermore, the curing temperature in step (3) is 15-25° C., and the relative humidity is 80%-98%.

[0023] The technical principle of the present invention is: by in-situ growth of Fe on a foam nickel substrate loaded with reduced graphene oxide 2 O 3 Nanocubes, the loading of reduced graphene oxide can significantly improve the conductivity and cycling performance of the composite electrode, Fe 2 O 3 It can contribute part of the pseudocapacitance and utilize the synergistic effect between the two to improve the electrode reduction graphene oxide / Fe 2 O 3 Electrochemical properties of electrode materials.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] 1. Reduced Graphene Oxide / Fe of the Present Invention 2 O 3 The electrode material has low preparation cost and good electrochemical performance. It is achieved by in situ growth of Fe on a nickel foam matrix loaded with reduced graphene oxide. 2 O 3 Nanocube, Fe 2 O 3 The size of the nanocubes is about 50nm, growing on graphene nanosheets, reducing the agglomeration of graphene nanosheets. At the same time, graphene can also prevent Fe 2 O 3 The volume expansion of the nanocubes and the synergistic effect of the two improve the reduced graphene oxide / Fe 2 O 3 Electrochemical properties of electrode materials;

[0026] 2. The present invention adds K to the cement-based composite material 3 [Fe(CN) 6 ], introducing redox reaction in cement solid electrolyte, using redox reaction of Fe(CN) 6 3- / Fe(CN) 6 4- The high solubility and electrochemical activity of the material can significantly increase the total capacitance of the energy storage device without affecting the mechanical properties.

[0027] 3. The present invention reduces graphene oxide / Fe 2 O 3As electrodes, the redox cement composites as solid electrolytes are used to prepare extended voltage and high-performance energy storage devices with a wide voltage window and high energy density.

[0028] 4. The energy storage devices prepared by the present invention can be connected in series to power a small LED bulb for 260 seconds, and are expected to be put into practical use in the field of construction in the future. The present invention can provide a promising strategy for the design of high-performance, low-cost energy storage technology in the field of civil engineering energy storage. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The reduced graphene oxide / Fe prepared by the present invention 2 O 3 X-ray powder diffraction pattern of the electrode;

[0030] Figure 2 The reduced graphene oxide / Fe prepared by the present invention 2 O 3 Scanning electron microscopy images of electrodes;

[0031] Figure 3 The reduced graphene oxide / Fe prepared in Examples 1, 2, 3, 4 and 5 2 O 3 Electrode cyclic voltammetry curve;

[0032] Figure 4 The reduced graphene oxide / Fe prepared in Examples 1, 2, 3, 4 and 5 2 O 3 Graph of electrode area capacitance versus current density;

[0033] Figure 5 Compressive strength and K of the redox cement-based electrolytes prepared in Examples 1, 2, 3, 4 and 5 3 [Fe(CN) 6 ] content;

[0034] Figure 6 The constant current charge and discharge curves of the redox cement-based electrolytes prepared in Examples 1, 2, 3, 4 and 5;

[0035] Figure 7 AC impedance diagrams of the redox cement-based electrolytes prepared in Examples 1, 2, 3, 4 and 5;

[0036] Figure 8 The constant current charge and discharge curve of the energy storage device prepared in Example 3;

[0037] Fig. 9 This is an energy comparison diagram of the energy storage device prepared in Example 3;

[0038] Fig.10 This is a test diagram of the cycle stability of the energy storage device prepared in Example 3;

[0039] Fig.11 The cyclic voltammetry curve of the series module of the energy storage device prepared in Example 3;

[0040] Fig.12 This is a schematic diagram of the structure of the iron-based solid-state energy storage device prepared by the present invention. DETAILED DESCRIPTION

[0041] The present invention will be described in detail below with reference to the accompanying drawings and embodiments. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

[0042] The reagents used in the following examples are all commercially available reagents, among which polyacrylic acid is purchased from Aladdin, with an average molecular weight of MW ≈ 3000 and a concentration of 50%. The various equipment used in the following examples are all commercially available equipment.

[0043] The test conditions for the mechanical properties and electrochemical properties of the iron-based solid-state energy storage device prepared by the present invention are as follows:

[0044] (1) During the mechanical property test, the size of the cement-based electrolyte mold was 40 mm × 40 mm × 40 mm. A YAW-300E fully automatic pressure testing machine was used with a loading speed of 2.4 kN / s. Six samples were tested in each group and the average value was taken.

[0045] (2) During the electrochemical performance test, the size of the iron-based solid-state energy storage device was 10 mm × 10 mm × 5 mm, and the cyclic voltammetry (CV), constant current charge and discharge (DC) of the electrode and the cyclic voltammetry (CV), alternating current impedance (EIS) and constant current charge and discharge (DC) of the structural supercapacitor were tested using a CHI660C electrochemical workstation. Before the test, the energy storage device was in a saturated water state.

[0046] The preparation steps of the iron-based solid-state energy storage device of the present invention are as follows:

[0047] (1) Reduced graphene oxide / Fe 2 O 3 Preparation of the electrode: ferric chloride dihydrate, sodium acetate, deionized water and ethanol are mixed and stirred to obtain a yellow mixed solution; graphene oxide is ultrasonically dispersed in deionized water to obtain a graphene oxide suspension, which is then coated on the surface of a nickel foam substrate, and placed in a vacuum drying oven for drying to obtain a nickel foam coated with graphene oxide on the surface; then the nickel foam coated with graphene oxide on the surface and the mixed solution are placed together in the lining of a reactor, and the reactor is placed in an oven for hydrothermal reaction to obtain reduced graphene oxide / Fe 2O 3 Semi-finished electrode; finally, the graphene oxide / Fe 2 O 3 The electrode semi-finished product was washed with ethanol and deionized water for 3-5 times, and dried in a vacuum drying oven to obtain reduced graphene oxide / Fe 2 O 3 electrode;

[0048] (2) Preparation of redox cement-based electrolyte: Polyacrylic acid, potassium hydroxide and K 3 [Fe(CN) 6 ] is dissolved in deionized water, and stirred evenly to obtain a polyacrylic acid mixed solution; the polyacrylic acid mixed solution is then mixed with cement and stirred evenly, and then poured into a mold to obtain a flowing redox cement-based electrolyte;

[0049] (3) Reducing the reduced graphene oxide / Fe 2 O 3 The electrodes are inserted into both sides of the mold containing the redox cement-based electrolyte in a flowing state obtained in step (2), vibrated for 2-5 minutes to make the redox cement-based electrolyte dense, and then placed in a curing room for curing, curing, and demolding to obtain the iron-based solid-state energy storage device.

[0050] Example 1

[0051] (1) Graphene oxide is ultrasonically treated in deionized water for 1 hour to obtain a well-dispersed graphene oxide suspension with a concentration of 10 mg / mL, the graphene oxide suspension is coated on the surface of nickel foam, and then placed in a 60°C oven for drying for 2 hours to obtain graphene oxide-coated nickel foam, and then the graphene oxide-coated nickel foam is immersed in a yellow mixed solution obtained by mixing ferric chloride dihydrate, sodium acetate, deionized water and ethanol and stirring them evenly, and then placed in a 100 ml high-pressure reactor for hydrothermal reaction at a hydrothermal temperature of 190°C and a hydrothermal time of 12 hours to obtain reduced graphene oxide / Fe 2 O 3 The electrode semi-finished product was finally washed 4 times in ethanol solution and deionized water respectively, and dried in a vacuum drying oven at 60°C for 4 h to obtain reduced graphene oxide / Fe 2 O 3 Electrode. Among them, the reduced graphene oxide and Fe 2 O 3 The concentrations were 0.16 mg cm -2 and 0.94 mg cm -2 ;

[0052] (2) 40 g of polyacrylic acid, 20 g of potassium hydroxide, and 64 g of deionized water were weighed and mixed and stirred evenly, and then placed together with 200 g of cement in a cement slurry mixing kettle, and stirred evenly for 10 min to obtain a cement-based composite material mixture, which was then poured into a 10 cm × 10 cm × 0.5 cm cubic mold to obtain a flowing redox cement-based electrolyte;

[0053] (3) The reduced graphene oxide / Fe prepared in step (1) 2 O 3 The electrodes are placed on both sides of the redox cement-based electrolyte prepared in step (2) and vibrated on a vibration table for 2 minutes to make the redox cement-based electrolyte compact, thereby obtaining an energy storage device; the device is then demoulded after being cured indoors for 24 hours, and placed in a curing room at a temperature of 20° C. and a relative humidity of 95% to cure to the corresponding age for compressive strength testing, and cured for 28 days for electrochemical performance testing.

[0054] Example 2

[0055] The difference from the preparation method of Example 1 is that 40g polyacrylic acid, 20g potassium hydroxide, 0.4g K 3 [Fe(CN) 6 ] and 64 g of deionized water were mixed and stirred evenly, and then placed together with 200 g of cement in a cement slurry stirring pot and stirred evenly for 10 min to obtain a redox cement-based electrolyte.

[0056] Example 3

[0057] The difference from the preparation method of Example 1 is that 40g polyacrylic acid, 20g potassium hydroxide, 0.8g K 3 [Fe(CN) 6 ] and 64 g of deionized water were mixed and stirred evenly, and then placed together with 200 g of cement in a cement slurry stirring pot and stirred evenly for 10 min to obtain a redox cement-based electrolyte.

[0058] Example 4

[0059] The difference from the preparation method of Example 1 is that 40g polyacrylic acid, 20g potassium hydroxide, 1.2g K 3 [Fe(CN) 6 ] and 64 g of deionized water were mixed and stirred evenly, and then placed together with 200 g of cement in a cement slurry stirring pot and stirred evenly for 10 min to obtain a redox cement-based electrolyte.

[0060] Example 5

[0061] The difference from the preparation method of Example 1 is that 40g polyacrylic acid, 20g potassium hydroxide, 1.6g K 3[Fe(CN) 6 ] and 64 g of deionized water were mixed and stirred evenly, and then placed together with 200 g of cement in a cement slurry stirring pot and stirred evenly for 10 min to obtain a redox cement-based electrolyte.

[0062] Figure 1 The reduced graphene oxide / Fe prepared in Examples 1, 2, 3, 4 and 5 2 O 3 X-ray powder diffraction pattern of the electrode. The diffraction peaks at 18.1°(012), 30.2°(104), 35.6°(110), 43.9°(113) and 54.1°(116) are consistent with Fe 2 O 3 The standard PDF card (JPCDF39-1346) matches well. The characteristic peak of graphite oxide at ≈11° is missing, indicating that graphite oxide is reduced during the hydrothermal reaction.

[0063] Figure 2 The reduced graphene oxide / Fe prepared in Examples 1, 2, 3, 4 and 5 2 O 3 Scanning electron microscope image of the electrode. The image shows the prepared Fe 2 O 3 The microscopic morphology is nanocubes with a size of about 50nm, grown on graphene nanosheets, reducing the agglomeration of graphene nanosheets. In turn, graphene can prevent Fe 2 O 3 The volume expansion of the nanocubes and the synergistic effect of the two improve the reduced graphene oxide / Fe 2 O 3 Electrochemical properties of electrode materials.

[0064] Figure 3 The reduced graphene oxide / Fe prepared in Examples 1, 2, 3, 4 and 5 2 O 3 Cyclic voltammetry curves of the electrode at different scan rates. -1 = and the scanning rate. It can be seen that the reduced graphene oxide / Fe 2 O 3 The voltage window of the electrode is (-1.1) ~ (-0.1) V, and all CV curves are quasi-rectangular, indicating that the capacitance of the electrode comes from the electrochemical double layer capacitance (EDLC) of the electrolyte ions adsorbed on the graphene surface and the Fe 2 O 3 The effect of pseudocapacitance.

[0065] Figure 4 The reduced graphene oxide / Fe prepared in Examples 1, 2, 3, 4 and 5 2 O3 The relationship between the area capacitance and current density of the electrode. It can be seen that as the current density increases, the area capacitance decreases. 2 O 3 Electrode at 1mAcm -2 The area capacity is the largest at 417.0 mF cm -2 , even at 5mA cm -2 At a high current density, the reduced graphene oxide / Fe 2 O 3 The electrode can still provide 282.6mF cm -2 Large area capacitors.

[0066] Figure 5 Compressive strength and K of the redox cement-based electrolytes prepared in Examples 1, 2, 3, 4 and 5 3 [Fe(CN) 6 ] content. Obviously, with the extension of curing age, the compressive strength of the sample increases. This result also proves that the porosity of the redox active cement composite material decreases with cement hydration. 3 [Fe(CN) 6 As the content of K increases from 0 to 0.08 M, the compressive strength of the redox-active cement composite material increases slightly from 11.72 MPa to 12.8 MPa after 28 days of curing, indicating that a small amount of K 3 [Fe(CN) 6 ] has little effect on the compressive strength.

[0067] Figure 6 The constant current charge-discharge curves of the redox cement-based electrolytes prepared in Examples 1, 2, 3, 4 and 5 are shown in FIG. It can be seen from the figure that the discharge time of the redox cement-based electrolyte in Example 3 is the longest, which is due to the fact that K 3 [Fe(CN) 6 ]'s additional contribution to the reversible redox process, indicating that the redox cement-based electrolyte prepared in Example 3 has the most excellent electrochemical storage capacity.

[0068] Figure 7 The AC impedance spectra of the redox cement-based electrolytes prepared in Examples 1, 2, 3, 4 and 5. All curves consist of a semicircle in the high frequency region and a straight line in the low frequency region. The equivalent series resistance R is obtained from the x-intercept of the semicircle. s , represents the electrode / current collector contact resistance, electrolyte ionic resistance and electrode material internal resistance. The semicircular diameter in the high-frequency region represents the charge transfer resistance (R ct ). Example 3 Preparation of Redox Cement-Based Electrolyte R sThe lowest value is only 0.05 Ω, which is due to the low ionic resistance in the redox-active cement electrolyte.

[0069] Figure 8 The constant current charge-discharge curve of the energy storage device prepared in Example 3. At different current densities, the constant current charge-discharge curve is almost a symmetrical triangle, and the voltage drop IR is very small (0.046V), indicating that the energy storage device has a low equivalent series resistance (Rs) and ideal charge storage characteristics. 2 The large contact area between the abundant active materials and the electrolyte in the energy storage device exhibits a large area capacitance.

[0070] Fig. 9 This is an energy comparison diagram of the energy storage device prepared in Example 3. It can be seen from the figure that when the power density is 0.075mWcm -2 100cm 2 The energy density of the energy storage device is as high as 23.10 μWh cm -2 Perhaps this is because the enlarged electrode area allows the device to store more electrical energy.

[0071] Fig.10 This is a test diagram of the cycle stability of the energy storage device prepared in Example 3. Since the graphene substrate has abundant electrochemical sites in the composite electrode, the 100 cm 2 The energy storage device has good cycle stability. As shown in the figure, the capacity retention rate of the energy storage device is as high as 80.8% after 2000 cycles of constant current charge and discharge.

[0072] Fig.11 Cyclic voltammetry curve of the series module of the energy storage device prepared in Example 3. 2 The energy storage devices are connected in series, the voltage can reach 3V, and three 100cm 2 The modules with energy storage devices connected in series can generate a voltage of 4.5V. 2 The modules of energy storage devices connected in series were charged to 4.5 V and could drive a green light-emitting diode (LED) to emit light for 260 seconds, confirming its potential application as an energy storage device in the field of civil engineering.

[0073] Example 6

[0074] (1) Reduced graphene oxide / Fe 2 O 3 Electrode: Mix 0.676 g ferric chloride dihydrate, 2.028 g sodium acetate, 10 ml deionized water and 40 ml ethanol and stir to obtain a yellow solution; -1The graphene oxide suspension was coated on the surface of nickel foam and placed in the lining of the reactor together with the yellow solution after drying. The reactor was then placed in an oven at 190°C for 12 hours of hydrothermal reaction to obtain reduced graphene oxide / Fe 2 O 3 Electrode semi-finished product; Reduced graphene oxide / Fe 2 O 3 The electrode semi-finished product was washed 4 times in ethanol solution, then washed 4 times in deionized water, and then dried in a vacuum drying oven at 60 °C for 4 h to obtain reduced graphene oxide / Fe 2 O 3 Electrode, the concentration of reduced graphene oxide loaded on the surface of nickel foam is 0.16 mg cm -2 and Fe 2 O 3 The concentration is 0.94 mg cm -2 .

[0075] (2) Redox cement-based electrolyte: weigh 40 g of 50% polyacrylic acid, 20 g of potassium hydroxide and K 3 [Fe(CN) 6 ]1.4g was mixed and dissolved in 64g deionized water, and stirred for 60min to obtain a uniform polyacrylic acid mixed solution; then, the polyacrylic acid mixed solution was mixed with 200g cement and stirred for 30min and poured into a 10cm×10cm×0.5cm mold to obtain a flowing redox cement-based electrolyte.

[0076] (3) Preparation of energy storage device: The reduced graphene oxide / Fe prepared above 2 O 3 The electrodes were placed on both sides of the redox cement-based electrolyte, placed on a vibration table and vibrated for 2 minutes to make the redox cement-based electrolyte dense, and finally placed in a curing room with a temperature of 20° C. and a relative humidity of 95% for curing to obtain an energy storage device.

[0077] Example 7

[0078] The difference from Example 6 is that: 40 g of 50% polyacrylic acid, 20 g of potassium hydroxide and K 3 [Fe(CN) 6 ] 2.0g was mixed and dissolved in 64g of deionized water, and stirred for 60min to obtain a uniform polyacrylic acid mixed solution; then, the polyacrylic acid mixed solution was mixed with 200g of cement and stirred for 30min and poured into a 10cm×10cm×0.5cm mold to obtain a flowing redox cement-based electrolyte.

[0079] In summary, the iron-based solid-state energy storage device prepared by the present invention has excellent electrochemical properties and good mechanical properties.

[0080] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. An iron-based solid-state energy storage device, characterized in that: The invention comprises a redox cement-based electrolyte and a reduced graphene oxide / Fe2O3 electrode; the reduced graphene oxide / Fe2O3 electrode is composed of foamed nickel, reduced graphene oxide and Fe2O3; the redox cement-based electrolyte is a cement-based composite material containing polyacrylic acid, potassium hydroxide, K3[Fe(CN)6] and cement; the redox cement-based electrolyte is located between two reduced graphene oxide / Fe2O3 electrodes.

2. The iron-based solid-state energy storage device according to claim 1, characterized in that: The cement is silicate cement.

3. The iron-based solid-state energy storage device according to claim 1, characterized in that: The mass ratio of cement, polyacrylic acid, potassium hydroxide, K3[Fe(CN)6] and deionized water in the redox cement-based electrolyte is (100-300):(20-80):(10-50):(0-4):(15-90).

4. A method for preparing an iron-based solid-state energy storage device as claimed in claim 1, characterized in that: The following steps are involved: (1) Preparation of reduced graphene oxide / Fe2O3 electrode: ferric chloride dihydrate, sodium acetate, deionized water and ethanol are mixed and stirred to obtain a mixed solution; graphene oxide is ultrasonically dispersed in deionized water to obtain a graphene oxide suspension, which is then coated on the surface of a foamed nickel substrate, and dried to obtain a foamed nickel substrate coated with graphene oxide; then the foamed nickel substrate coated with graphene oxide is subjected to a hydrothermal reaction with the mixed solution to obtain a reduced graphene oxide / Fe2O3 electrode semi-finished product; finally, the reduced graphene oxide / Fe2O3 electrode semi-finished product is washed and dried to obtain a reduced graphene oxide / Fe2O3 electrode; (2) Preparation of a redox cement-based electrolyte: firstly, polyacrylic acid, potassium hydroxide and K3[Fe(CN)6] are dissolved in deionized water, and stirred to obtain a polyacrylic acid mixed solution; then, the polyacrylic acid mixed solution is mixed with cement, stirred to obtain a redox cement-based electrolyte in a flowing state; (3) inserting the reduced graphene oxide / Fe2O3 electrodes obtained in step (1) into both sides of a mold containing the flowing redox cement-based electrolyte obtained in step (2), and then placing them in a curing room for curing, curing, and demolding to obtain the iron-based solid-state energy storage device.

5. The method for preparing an iron-based solid-state energy storage device according to claim 4, characterized in that: The mass ratio of ferric chloride dihydrate, sodium acetate, deionized water and ethanol in the mixed solution described in step (1) is (0.338-1.014):(1.014-3.042):(5-40):(15-50), and the stirring time of the mixed solution is 40-90 min.

6. The method for preparing an iron-based solid-state energy storage device according to claim 4, characterized in that: The concentration of the graphene oxide suspension described in step (1) is 5 to 20 mg mL -1 .

7. The method for preparing an iron-based solid-state energy storage device according to claim 4, characterized in that: The drying temperature of the nickel foam coated with graphene oxide on the surface described in step (1) is 40-80° C., the temperature of the hydrothermal reaction is 160-200° C.; the time of the hydrothermal reaction is 8-20 hours; the drying temperature of the reduced graphene oxide / Fe2O3 electrode semi-finished product is 40-60° C., and the drying time is 2-6 hours.

8. The method for preparing an iron-based solid-state energy storage device according to claim 4, characterized in that: The concentration of reduced graphene oxide loaded on the surface of the nickel foam described in step (1) is 0.05-0.5 mg·cm -2 The Fe2O3 concentration on the surface of nickel foam is 0.5-2 mg·cm -2 .

9. The method for preparing an iron-based solid-state energy storage device according to claim 4, characterized in that: The stirring time of the polyacrylic acid mixed solution and cement in step (2) is 5 to 30 minutes.

10. The method for preparing an iron-based solid-state energy storage device according to claim 4, characterized in that: The curing temperature in step (3) is 15-25° C., and the relative humidity is 80%-98%.

Citation Information

Patent Citations

  • Supercapacitor based on transition metal sulfide / nitrogen doped graphene and ferric oxide / graphene

    CN107134372A

  • Pouch type super capacitor, positive electrode material, and negative electrode material

    JP2021040078A